Transformasi Arah Strategis Sekolah Melalui Lokakarya Peninjauan Visi, Misi, dan Tujuan - Anna Maria (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The workshop to review the vision, mission and goals (VMT) at Santa Maria High School in Pekanbaru was held to ensure alignment between the school's strategic direction and developments in the educational environment, the Merdeka Belajar (Freedom of Learning) policy, and the values promoted by the school and the Foundation. The purpose of this activity was to increase the understanding and participation of all stakeholders and school members in reviewing a VMT that is relevant, contextual, and future-oriented. The methods used included a participatory approach through group discussions, SWOT analysis of the institution, and collaborative reformulation of the vision and mission statements. The results of the activity showed an increase in strategic awareness and commitment among school members towards the direction of institutional development. This workshop had a positive impact on improving the alignment of school strategies in realising the student profile and strengthening a quality-oriented organisational culture.